New Method for Building Vector of Diagnostic Signs to Classify Technical States of Marine Diesel Engine by Torsional Vibrations on Shaft-Line - Luu, Do Duc; Hanh, Cao Duc; Tru, Nguyen Xuan (Sustainable Marine Structures, 2020)
Vector of diagnostic signs (VDS) using torsional vibration (TV) signal on the main propulsion plant (MPP) is the vector of z maxima (or minima) values of the TV signal in accordance with the cylinder firing orders. The technical states of the marine diesel engine (MDE) include R= z+1 classes and are presented in z-dimensional space coordinate of VDS. The presentation of Dk, k=1÷R using z diagnostic signs (Vi, i=1÷z) is nonfigurative and quite complicated. This paper aims to develop a new method for converting VDS from z-dimensional to 2-dimensional space (two-axes) based on the firing orders of the diesel cylinders, as an equivalent geometrical sign of the all diagnostic signs. The proposed model is useful for presenting a technical state Dk in two-dimensional space (x, y) for better visualization. The paper verifies the simulation of the classification illustration of the 7–state classes for the MDE 6S46-MCC, installed on the motor vessel (MV) 34000DWT, using the new above mentioned method. The seven technical state classes (for 6-cylinder MDE,z=6) are drawn separately and visually in the Descartes. The received results are valuable to improve smart diagnostic system for analyzing normal/misfire states of cylinders in operation regimes. ER